Drivers and motives for membership at the Southbank Centre, a mixed arts venue in London, UK. Issue 1 (11th November 2013) - Slater, Alix; Armstrong, Kate
<x xml:space="preserve">Abstract</x> The primary purpose of this study is to understand the drivers and motives for purchasing and retaining membership of the Southbank Centre (SBC), an internationally acclaimed mixed arts centre in London, UK. Data were collected using a qualitative approach, and members were recruited to one of five focus groups according to their past booking history: 1) contemporary bookers; 2) visual art bookers; 3) classical bookers; 4) non‐bookers; and 5) across art form bookers. The results suggest that individuals commit to membership with SBC primarily for pragmatic, overt motives that they evaluate the value of their membership on, such as hard copies of the programme in advance, being able to secure and book tickets before the general public and unlimited and flexible access to the Hayward Gallery. The transcripts did however reveal latent motives such as aesthetics, cultural enrichment and attachment to SBC as an institution prior to joining the membership scheme, without which, the pragmatic motives would not be acted upon. There was a small group of participants whose original pragmatic motives for becoming a member had shifted to emotional motives including prestige, a sense of belonging and altruism. Further research is required to find out if these motives cross art form, venue and geographical location. Copyright © 2013 John Wiley & Sons, Ltd.